KONFLIK BATIN TOKOH RARAS DALAM NOVEL TABULARASA KARYA RATIH KUMALA - Sari, Winda Pramita; Bahardur, Iswadi; Hartati, Yulia Sri (Pendidikan Bahasa Indonesia, 2014)
This Study hav some backgrounds, th first, different characters of human caused a conflict happened in th figuresâs life named Raras in tabularasa novel created by Ratih Kumala revealed the conflicts in a figureâs life named Raras who is against the surrounding where it didânt support her personality. The third, the heart conflict is usually not really a part from psychological aspect of the figure, they are id, ego and super ego. The purpose of this research are (1) describing the caused of the figureâs Raras heart conflicts in tabularasa novel by Ratih Kumala, (2) describing th matter that influenced of the figureâs Raras heart conflict in tabularasa novel Ratih Kumala. This kind of the research is a qualitative by using descriptive method. The data in the research are the substances were supported the figureâs Raras heart conflicts happened in tabularasa novel by Ratih Kumala. The sources of data is taken from tabularasa novl by Ratih Kumala. The research was done by (1) reading and understanding the novel tabularasa by Ratih Kumala, (2) identifying and classifying the data of heart conflict of the figureâs Raras in the novel, (3) determining the heart conflict of the figureâs Raras looking at the view aspectâs id, ego and superego. (4) interpretation of the data, (5) proving and formulating the conclusion the result of the research show the figure Raras had been a heart conflict because of her love broke the social norm. Her relationship with Violet didnât convey, because Raras have never told her feeling to Violet.